FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KADAR GULA DARAH PADA PENDERITA DIABETES MELITUS TIPE 2 (STUDI DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU KOTA SEMARANG - Rahayu, Khasanah Budi; Saraswati, Lintang Dian; Setyawan, Henry (Fakultas Kesehatan Masyarakat, 2018)
Type 2 diabetes melitus is a disease that require continousÂ treatment and management in order to prevent complication.The aim of this research is to analysis correlation between some factors with blood glucose level in diabetes melitus patient. The method used in this research is observational with cross-sectional as study design which conduct in September until October 2017 at Puskesmas Kedungmundu area. The amount of sample is 65 of 173 diabetes patients. Sample is selected by simple random sampling. Data were collected through interview with questionnaire and measurement. Statistic analysis used in this research were Pearson Product Moment, Rank Spearman and Lambda. The result of research shows that 60% respondents have an uncontrollable blood glucose level. Furthermore bivariate analysis show that there is correlation between medication adherence, physical activity level, ans family supports with blood glucose level. Meanwhile there is no correlation between duration, obesity status, diet adherence, physical exercise type, physical exercise frequent and motivation level with blood glucose level. Based on the result of the research primary health care is suggested to give education not just to diabetes patients but to closest family of diabetes melitus patient. And as for diabetes patients is hoped to take medicine the doctors suggested.